2023
DOI: 10.1093/europace/euad326
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance–derived myocardial scar is associated with echocardiographic response and clinical prognosis of left bundle branch area pacing for cardiac resynchronization therapy

Zhongli Chen,
Xuan Ma,
Yuan Gao
et al.

Abstract: Aims Left bundle branch area pacing (LBBAP) is a novel approach for cardiac resynchronization therapy (CRT), but the impact of myocardial substrate on its effect is poorly understood. This study aims to assess the association of cardiac magnetic resonance (CMR)–derived scar burden and the response of CRT via LBBAP. Methods and results Consecutive patients with CRT indications who underwent CMR examination and successful LBBAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…However, in contrast to our results, this research demonstrated that septal scarring was more prevalent in patients with LBBB. 17 Our work supports the absence of a relationship between left ventricular fibrosis and conduction abnormalities. This was applicable to both segmental fibrosis (including septal fibrosis), as well as overall fibrosis, suggesting that QRS prolongation and ventricular fibrosis are distinct entities in patients with HF.…”
Section: Discussionsupporting
confidence: 81%
“…However, in contrast to our results, this research demonstrated that septal scarring was more prevalent in patients with LBBB. 17 Our work supports the absence of a relationship between left ventricular fibrosis and conduction abnormalities. This was applicable to both segmental fibrosis (including septal fibrosis), as well as overall fibrosis, suggesting that QRS prolongation and ventricular fibrosis are distinct entities in patients with HF.…”
Section: Discussionsupporting
confidence: 81%
“… 38 Notably, a lower scar burden has been identified as a strong predictor of LBBAP response, and pre-procedure cardiac magnetic resonance scar evaluation is proposed as an informative tool for assessing LBBAP CRT responders. 39 Additionally, intracardiac echocardiography–guided implantation during proximal LBBAP has been proposed to reduce procedure time and improve success rates. 40 …”
Section: Outline Of Conduction System Pacing (Hbp and Lbbap)mentioning
confidence: 99%